Characterization of Energetic Protons Generated in the ShenGuang-II UP Petawatt Laser Interactions with Foil Targets. (18th August 2021) - Liu, Huiya; Lei, Anle; Kang, Ning; An, Honghai; Xie, Zhiyong; Zhao, Yao; Zhou, Shenlei; Sun, Mingying; Zhu, Baoqiang; Wang, Wei; Zhu, Jianqiang
Abstract : The characterization of energetic protons generated in the ShenGuang-II UP petawatt laser interactions with foil targets has been systematically studied. The proton energy spectra and angular distributions are measured with a radiochromic film stack. It shows that the proton energy spectra have a Boltzmann distribution with temperature of about 2.8 MeV and cutoff energy of about 20 MeV. The divergence angles of protons vary from 10° to 60°, dependent on the proton energy. The proton source size and location are investigated via the proton point-projection mesh imaging. The proton virtual sources are found to locate tens to hundreds of microns in front of the foil target, depending on the proton energies. A Monte Carlo simulation estimates the diameter of the virtual proton source to be about 12 μ m for the protons with energy of 16.8 MeV, which is much smaller than the laser focus size of about 50 μ m. The spatial resolution of the 16.8 MeV proton imaging is quantified with the point spread function to be about 15 μ m, which is consistent with the proton virtual source size. These results will be important for the users conducting experiments with the protons as a backlighting source on the ShenGuang-II UP petawatt laser.